Optimization of fermentation conditions for green pigment production from Bacillus cereus M116 (MTCC 5521) and its pharmacological application. (3rd October 2013) - Banerjee, D.; Mondal, A.; Gupta, M.; Guha, A. K.; Ray, L.
<x xml:space="preserve">Abstract</x> Significance and Impact of the Study: This study demonstrated the optimum production of a biopigment (9‐methyl‐1, 4, 5, 8‐tetra‐azaphenanthrene) by fermentation of a complex medium with Bacillus cereus M116 (MTCC 5521) in submerged fermentation. This is the first investigation of toxicity and cytotoxicity activities of this biopigment. The study showed that the purified pigment had no toxicity to healthy albino mice but a high cytotoxicity activity in HL60 cancer cell line in vitro. The biopigment had further displayed dyeing capability to both solidified agar and cotton cloth. Therefore, it may represent a nontoxic and natural alternative to chemical dyes and pigments. <boxed-text content-type="graphic" id="lam12151-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>